Science education through Malaysian animation series - Sarif, Latifah; Syed-Abdullah, Sharifah Intan Sharina; Mohd Sufian Kang, Enio Kang (Macrothink Institute, 2022)
Animation is one of the multimedia elements that is able to express children's fantasies into reality. Animation is seen to be able to motivate and stimulate children's thinking in an effort to reduce the cognitive load during the learning process. Animation in science education has been used as an educational resource to support science learning for decades. However, most members of society consider animation to be merely a form of entertainment. Contrary to popular belief, animation is not just focused on entertainment alone, but also plays a huge role in the world of education. This study was conducted through a data analysis process from Miles et al. on three popular animation series published by local animation companies. An analysis was conducted to identify the elements of science education delivered through the published animated series. The results of the survey found that 33 episodes of the Upin & Ipin animated, 26 episodes of the Didie and Friends animated series and 14 episodes of the Alif and Sofia animated series contain elements of science education that can be utilized in primary school science education. This study was implemented so that community members make use of the animated series that are screened used to educate children through non-formal education as basic knowledge of science in children's daily lives. This study is also expected to give ideas to local animation companies to produce more animated series that have elements of Science education. This study is also able to help teachers to make use of the serial animations that have been published as the latest approach in the development of primary science curriculum.